Socio-Cultural Dynamics of Media Portraiture in Journalism on Military Operations - Anastasia N. Grishanina; Sofia V. Shchebenkova (Гуманитарный вектор)
The relevance of the study is due to the emergence of new forms of media images associated with the coverage of a special military operation conducted by Russia in Ukraine. The study of portraiture can be useful for identifying the criteria for the image of a person in demand by the reader during the revival of traditional values and universal factors of spirituality. The purpose of the research is to study strategies and tactics of portraying a person in emergency situations, especially in war zones, to identify problematic areas of journalistic portraiture at the present stage. The depiction of significant or notable figures of military operations helps the reader in understanding moral and spiritual strategies. In the perspective of the study is the media image of Yevgeny Prigozhin, a prominent and ambiguous figure of the special military operation. The object of the study was media texts about E. Prigozhin published in 2020–2023. By the example of the coverage of one of the key figures of the special military operation (SMO), the means of reproducing the portrait in the media are identified, the role and tasks of the media image are outlined, attempts are made to comprehend the presentation of information through the prism of preserving cultural heritage and values of society. The main research methods are determined based on the goals. The linguistic and cultural analysis revealed the most popular forms of media portraiture, as well as the role of narrative structure, categories of space and time, composition in the perception of the portrait. Content analysis made it possible to analyze the content, keywords and significant semantic fragments in a vast array of media texts. Intent analysis was used to study the intentions and motives of the authors of works that influence media discourse. The novelty of the research is in the study of the socio–psychological and moral aspects of the modern media portrait, since these characteristics increasingly need to be understood from the position of “do no harm”. The results of the study revealed the popular forms of depicting a person in a difficult life situation, showed the necessity and timeliness of depicting the spiritual and moral component of the behavioral characteristics of a media personality, identified the problem areas of the portraiture process in cases when journalists resort to manipulation by creating a portrait in the media. The authors also point to further promising areas of research into the process of media portraiture, which include the need to typologize a media portrait, identifying the relationship between portrait and situational personality characteristics, and the features of positioning value strategies in a rapidly changing world.